Benzyloxycarbonyldehydropeptides hydrogelators for drug delivery - Brandão, D. (2019)
New benzyloxycarbonyldehydropeptides hydrogelators were synthesized. Gelation was attained at 0.3 wt% and pH=7.3. The new hydrogel is promising for drug delivery applications.